THE GAMBLING CRIME PREVENTION EFFORTS - MAYASARI MUIN, AUDYNA; TENRI FAMAURI, ANDI; MARWAH; ALRIP, ISMAIL (Awang Long Law Review, 2020)
The crime of gambling is regulated in Article 303 and Article 303 bis of the Criminal Code (KUHP), this crime is included in the category of crimes against decency. The sanctions for gambling crimes stipulated in the Criminal Code are of an alternative nature, that is, they are punishable by the main punishment in the form of imprisonment or a fine, in which the punishment is based on the qualification of the act committed by the perpetrator. Prevention efforts that can be made against the prevalence of gambling cases, especially in Wajo Regency, use a criminological approach which consists of pre-emptive, preventive and regressive efforts. The form of preventive efforts taken is in the form of structuring laws and regulations, providing legal counseling to the public and optimal law enforcement against gambling crimes.